School value-added models for multivariate academic and non-academic outcomes: exploring implications for performance monitoring and accountability. Issue 3 (3rd July 2021) - Prior, Lucy; Goldstein, Harvey; Leckie, George
ABSTRACT: Education systems around the world increasingly rely on school value-added models to monitor school performance and hold schools to account. These models typically focus on a limited number of academic outcomes. We explore how the traditional multilevel modelling approach to school value-added models can be extended to simultaneously analyse multiple academic and non-academic outcomes and the implications of doing so for systems using student data to monitor schools and inform school accountability. We jointly model student attainment, absence, and exclusion data for schools in England. We find very different results across the three outcomes, in terms of the size and consistency of school effects, and the importance of adjusting for student and school characteristics. The results suggest the three outcomes are capturing fundamentally distinct aspects of school performance, all of which are therefore important for education systems to monitor and explore including in systems of school accountability.